A Note on Labor Productivity and Foreign Inward Direct Investment - Peter Egger; Michael Pfaffermayr (Austrian Institute of Economic Research (WIFO), 1999)
Foreign Direct Investment (FDI) is not only a transfer of capital, but a complex bundle of capital and firm-specific assets like production and management know-how. In particular, the transfer of production know-how improves overall productivity of FDI-receiving firms and to some extent also that of the other firms due to spillovers. From a host country's point of view this kind of productivity improvement forms an important contribution to overall growth. The present note uses a small panel of Austrian manufacturing sectors and investigates this hypothesis empirically. Using a fiexible CES-framework we indeed find significant productivity improving effects of inward FDL Furthermore, there is some evidence that FDI induces labor-augmenting productivity effects. Thus, the job creation potential of FDI highlighted in previous studies is likely to be overestimated.
Keywords: C33; D24; F21; F23; 330; labor productivity; foreign direct investment; panel econometrics; Auslandsinvestition; Arbeitsproduktivität; Theorie; Österreich